The Impact of Flexible Working Arrangements on Job Performance Through Work-Life Balance of Students Working on Social Media in Surabaya - Ernanda, Reza Dwi; Fazlurrahman, Hujjatullah (CV ODIS, 2023)
The impact of the pandemic caused by COVID-19 has led to changes in various aspects of life, including the economy and education. The increasing needs of life make students look for ways to meet these needs. The phenomenon of students carrying out dual roles, namely studying while working, is often found among students in Surabaya. Students tend to choose jobs in the field of social media because the time is flexible and can be adequately mastered. This study examines and analyzes the effect of flexible working arrangements on job performance through work-life balance. This research is a causality study with a quantitative approach. Determination of the sample using nonprobability sampling with purposive sampling technique. The number of samples in this study was 110 respondents, that is, students in Surabaya who work in the field of social media. The statistical analysis used is the Partial Least Squares with the help of SmartPLS 3.2.9 software. This study explains that flexible working arrangements positively and significantly affect employee job performance. A work-life balance also has a positive and significant impact on job performance. However, a work-life balance cannot mediate the relationship between flexible working arrangements and job performance.